2022
DOI: 10.1167/iovs.63.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Mechanotransduction via Yes-Associated Protein in Human Lamina Cribrosa Cells in Glaucoma

Abstract: Purpose Extracellular matrix stiffening is characteristic of both aging and glaucoma, and acts as a promoter and perpetuator of pathological fibrotic remodeling. Here, we investigate the role of a mechanosensitive transcriptional coactivator, Yes-associated protein (YAP), a downstream effector of multiple signaling pathways, in lamina cribrosa (LC) cell activation to a profibrotic, glaucomatous state. Methods LC cells isolated from glaucomatous human donor eyes (GLC; n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 77 publications
3
13
0
Order By: Relevance
“…By contrast, Lat B-mediated actin depolymerization failed to reduce αSMA-positive cells. Importantly, we found that TGFβ2-induced EndMT in HSC cells was potently blocked by pharmacologic YAP/TAZ inhibition with verteporfin in absence of light stimulation consistent with previous reports in non-ocular 6567 and ocular cells 51,68,69 ; significantly decreased fibronectin and actin stress fibers were noted ( Fig. 5A-D ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…By contrast, Lat B-mediated actin depolymerization failed to reduce αSMA-positive cells. Importantly, we found that TGFβ2-induced EndMT in HSC cells was potently blocked by pharmacologic YAP/TAZ inhibition with verteporfin in absence of light stimulation consistent with previous reports in non-ocular 6567 and ocular cells 51,68,69 ; significantly decreased fibronectin and actin stress fibers were noted ( Fig. 5A-D ).…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with this, we showed that TGFβ2 enhanced EndMT of HSC cells cultured atop tissue-mimetic ECM hydrogels, as indicated by increased formation of fibronectin and αSMA (Fig. 2D,E Importantly, we found that TGFβ2-induced EndMT in HSC cells was potently blocked by pharmacologic YAP/TAZ inhibition with verteporfin in absence of light stimulation consistent with previous reports in non-ocular [65][66][67] and ocular cells 51,68,69 ; significantly decreased fibronectin and actin stress fibers were noted (Fig. 5A-D).…”
Section: Discussionsupporting
confidence: 91%
“…By contrast, Lat B-mediated actin depolymerization failed to reduce αSMA-positive cells. Importantly, we found that TGFβ2-induced EndMT in HSC cells was potently blocked by pharmacological YAP/TAZ inhibition with verteporfin in absence of light stimulation consistent with previous reports in nonocular 65 67 and ocular cells 51 , 68 , 69 ; significantly decreased fibronectin and actin stress fibers were noted ( Figs. 5 A– 5 D).…”
Section: Discussionsupporting
confidence: 92%
“…Hippo signalling is a therapeutic target in cancer biology and inhibitors of YAP/TAZ, the downstream effectors of the Hippo pathway are attractive targets [ 103 , 104 ]. The inhibition of YAP with verteporfin in lamina cribrosa cells showed therapeutic benefits [ 105 ]. ER stress and the unfolded protein response (UPR) have also gained interest in glaucoma and ophthalmology as therapeutic targets [ 106 , 107 , 108 ].…”
Section: Discussionmentioning
confidence: 99%